Indigenous cattle breeds and factors enhancing their variation, potential challenges of intensification and threats to genetic diversity in Uganda - Kabi, Fredrick; Muwanika, Vincent B.; Masembe, Charles (Animal Genetic Resources, 2016)
Indigenous cattle support approximately 26.1 percent of Ugandan families through provision of food and income in addition to the supply of socio-cultural wealth and security. Cattle keepers have developed and maintained variations of indigenous cattle phenotypes and genotypes suited to their agro-ecological zones through traditional management practices and socio-cultural aspects. The Ankole (Bos taurus indicus), East African shorthorn Zebu (Bos indicus) and their crossbred cattle constitute the main indigenous breeds, adding up to 93.3 percent of the Ugandan herd. With intensions to increase productivity, state policies encourage livestock farmers to upgrade local genotypes towards high yielding exotic dairy cattle. This if not appropriately planned is likely to result into loss of local genetic diversity, well endowed with resilience to local climatic conditions, endemic diseases and feed resource constraints. Here in, we review literature related to indigenous cattle in Uganda including how diverse landscapes, local management practices and socio-cultural aspects have enriched patterns of indigenous cattle variations. Then we highlight potential challenges of intensive management, increased selection for higher productivity and threats to genetic diversity of indigenous cattle populations. Since indigenous cattlevary with landscapes and socio-cultural values, have taken decades to establish, efforts to save them through genetic diversity studies, conservation and farmers sensitization should be undertaken immediately
Keywords: Agro-pastoral and pastoral; Ankole, East African shorthorn zebu; genetic variation; intensification; Uganda